Secondary chordal resection with septal myectomy for treatment of symptomatic obstructive hypertrophic cardiomyopathy. (6th March 2021) - Ram, Eilon; Schwammenthal, Ehud; Kuperstein, Rafael; Jamal, Tamer; Nahum, Eyal; Sternik, Leonid; Raanani, Ehud
Abstract:  : OBJECTIVES: Left ventricular outflow tract obstruction causes symptoms of heart failure in most patients with hypertrophic cardiomyopathy. Resection of the secondary mitral valve (MV) chordae has recently been shown to move the MV apparatus posteriorly, thereby eradicating the outflow gradient. The aim of this study was to evaluate whether secondary chordal resection concomitant to septal myectomy improves outcomes. METHODS: Between 2005 and 2020, a total of 165 patients underwent septal myectomy without MV repair or replacement in our Medical Center. Secondary MV chordal resection was performed in 60 patients, and their outcomes were compared with those of the remaining 105 patients who did not undergo chordal resection (controls). Mean age was 61 ± 13 and 58 ± 16 years, respectively ( P  = 0.205). RESULTS: There were no in-hospital deaths throughout the entire cohort. Of those patients who underwent secondary chordal resection, New York Heart Association functional class decreased from 3 (interquartile range 2–3) preoperatively to 1 (interquartile range 1–2) postoperatively ( P  < 0.001), and resting outflow gradient decreased from 91 ± 39 mmHg to 13 ± 8 mmHg (86% change, P  < 0.001). Compared with controls, patients who underwent secondary chordal resection had a significant lower resting outflow gradient at follow-up (14 ± 7 mmHg vs 21 ± 15 mmHg, P  = 0.002). The rate of moderate or more than moderate mitral regurgitation at 5 years was 2% in the secondary chordal resection group and 5% in the controls (hazard ratio 1.05, confidence interval 0.11–10.32; P  = 0.965). CONCLUSIONS: In this observational study, we report that secondary chordal resection concomitant to septal myectomy for left ventricular outflow tract obstruction is safe, relieves heart failure symptoms and reduces left ventricular outflow tract gradient in appropriately selected patients.